Quantum Hall effect from the topological surface states of strained bulk HgTe. - Brüne, C; Liu, C; Novik, E; Hankiewicz, E; Buhmann, H; Chen, Y; Qi, X; Shen, Z; Zhang, S; Molenkamp, L (2011)
We report transport studies on a three-dimensional, 70-nm-thick HgTe layer, which is strained by epitaxial growth on a CdTe substrate. The strain induces a band gap in the otherwise semimetallic HgTe, which thus becomes a three-dimensional topological insulator. Contributions from residual bulk carriers to the transport properties of the gapped HgTe layer are negligible at mK temperatures. As a result, the sample exhibits a quantized Hall effect that results from the 2D single cone Dirac-like topological surface states.